Correction of Microstomia Reconstruction With the Use of Acellular Dermal Matrix for Buccal Reconstruction. Issue 3 (May 2019) - Wood, Benjamin C.; Mantilla-Rivas, Esperanza; Goldrich, Agnes; Boyajian, Michael K.; Oh, Albert K.; Rogers, Gary F.; Boyajian, Michael J.
Abstract : Abstract: Correction of microstomia is challenging with a high rate of recurrence. We report the successful treatment of microstomia using acellular dermal matrix (ADM) as an adjunct for intraoral lining with >1 year of follow-up. A 9-year-old international patient with severe immunodeficiency presented with severe microstomia because of recurrent oral infections. She had undergone 3 previous failed attempts to re-establish an adequate oral opening and was dependent on enteral nutrition via gastrostomy tube. She underwent release of the oral commissure scar contracture and orbicularis oris and the resultant mucosal defect was lined with ADM. A postoperative splint was used for 8 weeks. One-year follow-up demonstrated maintenance of the oral aperture with complete mucosalization of the ADM; the patient was able to resume oral diet and regular dental hygiene. Mucosal reconstruction with ADM is a viable alternative to local flaps and in this case exhibited minimal soft tissue contraction.